2021
DOI: 10.3390/dj9040046
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and Dentistry: A Literature Review on Risk Management during Dental Surgical Procedures

Abstract: Background: Pregnancy is a unique moment in a woman’s life, accompanied with several physiologic changes that have an impact on oral health. Aim of the study: The purpose of the present study was to conduct a critical review of published literature regarding pregnancy and dentistry, the most frequent oral diseases that are encountered during pregnancy, their correlation to adverse pregnancy events, and safe dental treatments that can be performed during pregnancy. Methods: A Medline/COCHRANE search was carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 109 publications
(49 reference statements)
0
25
0
3
Order By: Relevance
“…Currently, it has been universally acknowledged that non-surgical periodontal treatment during pregnancy is safe, although oral anti-inflammatory treatment during pregnancy did not significantly lessen adverse pregnancy outcomes ( 100 ). Furthermore, as a vital part of pregnancy health, reasonable intervention of oral diseases during pregnancy is beneficial to the physical and mental health of patients and can reduce the mother-to-child transmission of oral pathogens.…”
Section: The Effect Of Periodontal Therapy On Adverse Pregnancy Outcomesmentioning
confidence: 99%
“…Currently, it has been universally acknowledged that non-surgical periodontal treatment during pregnancy is safe, although oral anti-inflammatory treatment during pregnancy did not significantly lessen adverse pregnancy outcomes ( 100 ). Furthermore, as a vital part of pregnancy health, reasonable intervention of oral diseases during pregnancy is beneficial to the physical and mental health of patients and can reduce the mother-to-child transmission of oral pathogens.…”
Section: The Effect Of Periodontal Therapy On Adverse Pregnancy Outcomesmentioning
confidence: 99%
“…About the safety of obtaining dental radiographs in pregnant women, the majority 125 (82.2%) of the ANC providers were not aware that it is safe to obtain dental radiographs in pregnant women and use of dental radiographs, if necessary, after the first trimester does not pose any risk to the developing fetus [58], however, it is recommended to use protective lead aprons and thyroid collar to shield the sensitive areas. This kind of misconception could however be overcome among ANC providers by continuous services professional training and collaboration among different professionals within the different health facilities.…”
Section: Adoption Of Oral Health Promotion By Respondentsmentioning
confidence: 99%
“…It was reported in the literature that oral biofilm might induce surface changes in dental restorative materials, leading to their chemical degradation and thus a higher chance for the dental fillings to develop marginal percolation and other defects [ 12 ]. It was also reported that chewing gum might lead to leaching of chemical compounds of resin-based composites [ 13 ]. It is well known that any change in the architecture of the oral cavity may interfere with the whole oral equilibrium, disturbing it at different levels (e.g., muscles, teeth, TMJ) [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%